Organizational Pro-Environmental Behavior (A Case Study of Harapan dan Do’a Hospital, Bengkulu City) (The Manager Review, 2025)
This study aims to describe and explore factors related to awareness of consequences, ascription of responsibility, and personal norms in achieving aspects of pro-environmental behavior according to Kaiser at Harapan and Doa Hospitals in Bengkulu. Pro-environmental behavior, which aims to reduce negative impacts on the environment or improve environmental quality, involves actions like energy conservation, efficient mobility and transportation, waste reduction, recycling, environmentally conscious consumer choices, and participation in conservation efforts. Pro-environmental behavior depends on individuals' environmental awareness, knowledge, and willingness to act for the benefit of society, the environment, and future generations. In developing countries, environmental awareness is often low due to a cultural emphasis on economic welfare over sustainability. Increasing pro-environmental behavior is crucial to supporting sustainable development and improving quality of life. The findings reveal that pro-environmental behavior among employees at RSHD Bengkulu City is evident through three key factors: awareness of consequences, ascription of responsibility, and personal norms. Employees' environmental awareness drives them to use recycled medical products and reduce paper through digital documentation. Their sense of responsibility is reflected in their use of energy-efficient technology and commitment to turning off equipment when not in use. Strong personal norms further promote sustainability through eco-friendly product choices, coworker education, and involvement in green procurement. This demonstrates the employees’ commitment to environmental sustainability and shows that pro-environmental behavior is achievable through developing individual awareness, responsibility, and norms aligned with sustainability principles.